Socialistična in demokratična cenzura v Sloveniji - Troha, Gašper (Primerjalna književnost, 2008)
Recent lawsuits against writers (cf. Pikalo and Smolnikar) have not only raised the issue of relations between literature and reality, but also have illustrated an interesting transformation in censorship practices in Slovenia after the fall of communism. Under communism the authorities usually suppressed literary texts or theatre performances, a practice that enabled theartists to continue with their work while bringing them a considerable increase in popularity. The article analyses the case of the show Pupilija papa Pupilo pa Pupilčki, which stirred up significant controversy both in 1969 and in 2006, when it was restaged/reconstructed. Differences in reactions to this show demonstrate changes in formal and informal control over cultural events.
Keywords: Jovanović, Dušan, 1939-; Hrvatin, Emil; literatura in cenzura; slovenska dramatika; slovensko gledališče; gledališke predstave; rekonstrukcije